Mythos ebook - Fry, Stephen (Mythos, 2019)
Here are the thrills, grandeur, and unabashed fun of the Greek myths, stylishly retold by Stephen Fry. The legendary writer, actor, and comedian breathes life into ancient tales, from Pandora's box to Prometheus's fire, and transforms the adventures of Zeus and the Olympians into emotionally resonant and deeply funny stories, without losing any of their original wonder. Classical artwork inspired by the myths and learned notes from the author offer rich cultural context.